Struthanthus vulgaris ointment prevents an over expression of inflammatory response and accelerates the cutaneous wound healing. (22nd August 2016) - dos Santos Gramma, Luciane Souza; Marques, Franciane Martins; Vittorazzi, Cátia; de Andrade, Thiago Antônio Moretti; Frade, Marco Andrey Cipriani; de Andrade, Tadeu Uggere; Endringer, Denise Coutinho; Scherer, Rodrigo; Fronza, Marcio
Abstract: Ethnopharmacological relevance: Struthanthus vulgaris (Vell.) Mart. (Loranthaceae) has been largely used in traditional folk medicine in Brazil as an anti-inflammatory agent and to treat various skin disorders, including wounds. Aims of the study: To investigated the influence of 5% Struthanthus vulgaris ointment during cutaneous wound healing in rats. Materials and methods: Twenty Wistar rats were used in each group according the daily treatment, S. vulgaris 5% ointment (SV 5%) and vehicle control groups. Four full thicknesses wounds were punched in back side skin of each animal, and five animals were sacrificed after 2, 7, 14 and 21 days after surgery for histological, immunological and biochemical analysis. Results: A significant wound closured area in the S. vulgaris 5% group of about 38% and 35% as compared to 19% and 21% in the control group was observed after 2 and 5 days, respectively. Histological and biochemical analysis of the skin biopsies showed that S. vulgaris treated wounds exhibited increased granulation tissue and regulated the inflammatory response by modulating the release of pro and anti-inflammatory cytokines like IL-1α, TNF-α and IL-10, nitric oxide and, growth factors like TGF-β. Moreover, S. vulgaris showed a marked and robust increase in the deposition and organization of collagen fibers in the wounds, and improve the quality of the scar tissue. Conclusions: Altogether these data revealed that S. vulgaris seems to prevent an over expression of inflammation and accelerates wound epithelialization and might be beneficial for treating healing disorders. Graphical abstract: